Glucagon-like peptide-1 as a treatment for chemotherapy-induced mucositis. Issue 12 (20th October 2012) - Kissow, Hannelouise; Hartmann, Bolette; Holst, Jens Juul; Poulsen, Steen Seier
Abstract : Background: Glucagon-like peptide-2 (GLP-2) has been suggested for the treatment of mucositis, but the peptide has also been shown to accentuate colonic dysplasia in carcinogen-treated mice. Recently, an effect on intestinal growth was discovered for glucagon-like peptide-1 (GLP-1), Objective: To determine whether endogenous GLP-1 contributes to the healing processes and if exogenous GLP-1 has a potential role in treating mucositis. Methods: Mice were injected with 5-fluorouracil (5-FU) or saline to induce mucositis and were then treated with GLP-1, GLP-2, GLP-2 (3-33), exendin (9-39) or vehicle. The mice were sacrificed 48 or 96 h after the 5-FU injections. The end points were intestinal weight, villus height, proliferation and histological scoring of mucositis severity. Rats were injected with 5-FU or saline, and after 48 h, blood was drawn and analysed for GLP-1 and GLP-2 concentration. Results: GLP-1 and GLP-2 significantly prevented the loss of mucosal mass and villus height and significantly decreased the mucositis severity score in the duodenum and jejunum 48 h after chemotherapy. The effect was equivalent. Exendin (9-39) reduced the intestinal weight 96 h after chemotherapy. The GLP-1 levels in blood were increased more than 10-fold, and GLP-2 levels were increased sevenfold. Conclusions: GLP-1 and GLP-2 were secreted after intestinal injury, and recovery was delayed after treatment with exendin (9-39), indicating an important role for the peptides in the protection of the intestine from injury. GLP-1 treatment ameliorated mucositis, which suggests that mucositis and other acute intestinal disorders might benefit from treatment with GLP-1 analogues.